2015
DOI: 10.1177/0267659114567556
|View full text |Cite
|
Sign up to set email alerts
|

A paediatric ECMO case of plasma leakage through a polymethylpentene oxygenator

Abstract: Polymethylpentene (PMP) oxygenators, utilised for ECMO, are commonly believed to be resistant to plasma leakage. Whilst uncommon, plasma leakage has been previously reported with PMP fibres, both in vivo and in vitro. We describe a paediatric ECMO case during which plasma leakage occurred and oxygenator function gradually deteriorated, ultimately necessitating device replacement. To our knowledge, this is the first case of plasma leakage described using a PMP device during paediatric ECMO. Subsequent investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Contemporary long-term oxygenators marketed as being plasma-tight have been a key advancement in ECMO technology. There is one case report of a plasma-tight membrane experiencing plasma leakage described by Gill et al, 10 who observed a collection of fluid at the gas egress of a Medos Hilite LT oxygenator. As this fluid accumulated, an increase in fresh gas flow was required due to retained CO 2 and presumed failing gas permeability.…”
Section: Artificial Gas Exchangementioning
confidence: 99%
“…Contemporary long-term oxygenators marketed as being plasma-tight have been a key advancement in ECMO technology. There is one case report of a plasma-tight membrane experiencing plasma leakage described by Gill et al, 10 who observed a collection of fluid at the gas egress of a Medos Hilite LT oxygenator. As this fluid accumulated, an increase in fresh gas flow was required due to retained CO 2 and presumed failing gas permeability.…”
Section: Artificial Gas Exchangementioning
confidence: 99%
“…On purely theoretical grounds, the absence of a dense barrier between the gas and the blood stream could lead to the formation of micro-emboli in the blood that could expose ECMO patients to serious hazards. As it can be estimated from Equation (1), for polyolefin membranes with maximal pore size a tenth of a micron large, microbubble formation may occur only when the oxygenator is operated at high gas pressures (e.g., when gas flow rate is increased to recover some gas exchange capacity lost for plasma leakage) (Gill et al, 2015) or when pinholes are present in the membrane wall (i.e., with faulty membranes). In this study, micro-emboli formation was not investigated because experiments with faulty membranes were discarded and gas flow rate was not increased when plasma leakage occurred because the study was not focused on the characterization of the oxygenator gas exchange capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This study was designed to evidence the limits of using only the membrane maximal pore size to characterize the resistance to plasma breakthrough of ECMO devices, and to bring experimental evidence of the extent to which the whole membrane pore size distribution and the conditions under which an ECMO device is operated determine the occurrence of water breakthrough. In the clinics, the occurrence of plasma breakthrough is signaled by a decrease of the ECMO gas exchange capacity (e.g., Gill et al, 2015), an effectiveness parameter strongly dependent on the actual fluid dynamics of the ECMO device (Catapano et al, 2001). It is worthwhile noting that the methods used for this study permitted to characterize the occurrence of plasma breakthrough independent of measurements of the gas exchange across the membrane wall, hence of the actual ECMO module design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Puis et al 20 described a case of a young woman who needed immediate oxygenator exchange because of the detection of plasma leakage followed by a fall in performances of two parallelplaced oxygenators. Gill et al 21 reported a case of a 16-monthold boy who required venoarterial ECMO support for acute myocarditis. Plasma leakage started to occur since day 1, and by day 6, it was mandatory to replace the oxygenator.…”
Section: Is Sars-cov-2 Present In Blood?mentioning
confidence: 99%